Studies on thermal and viscoelastic properties of vinyl ester resin and its composites with glass fiber - Garay,André C. (2015)
Vinyl ester resins are widely used in sandwich composite structures. Because of their good resistance to chemicals, flexibility and easy processing, these sandwich are extensively applied in the marine sector. These composites are typically manufactured by liquid molding processes, especially infusion. In this study, RTM light was used to inject the polymeric resin into the mold cavity, flowing in the space between the impermeable core and the mold walls, where the fibrous medium was. In this process, viscosity, gel time and curing time of the resin are very important parameters. This work addressed the curing and post-curing characteristics of a vinyl ester resin, and also the characteristics of neat and reinforced vinyl ester using dynamic mechanical analysis (DMA). The increase in shear rate did not significantly influence resin viscosity within the studied range. Differential scanning calorimetry showed the efficiency of the post-curing stage, with the decrease in residual enthalpy. With DMA, it was possible to determine gel time and gel temperature, which yielded similar values to those found by the SPI (Society of the Plastics Industry) method, indicating that the simpler SPI method can be reliably used for that.